Tissue distribution and depletion of levamisole in sheep tissues - TYRPENOU (Α.Ε.ΤΥΡΠΕΝΟΥ) A. E.; XYLOURI-FRANGIADAKI (Ε.Μ. ΞΥΛΟΥΡΗ-ΦΡΑΓΚΙΑΔΑΚΗ) E. M.; FRANGIADAKIS (Μ.Γ. ΦΡΑΓΚΙΑΔΑΚΗΣ) G. M. (Journal of the Hellenic Veterinary Medical Society, 2017)
The subject-matter of this project was the residue distribution and depletion of levamisole in the sheep tissues after a single administration of levamisole hydrochloride and with final aim the appropriate withdrawal time determination, so that sheep tissues will be safe for human consumption. Levamisole hydrochloride was given per os with a single dose in the form of a tablet of the pharmaceutical product Tridicine™ 300 mg at the recommended therapeutic dose of 300 mg/40 kg body weight (b.w.), a quantitycorresponding to 7.5 mg levamisole per kg b.w. Five sampling points comprised of four sheep each one , were performed at 24 h, 96 h, 168 h, 240 h and 336 h after medication. Tissue samples of muscle, liver, kidney and fat were collected, packed and stored at 45°C until analysis. Levamisole was determined by high performance liquid chromatography (HPLC) and mean levamisole concentrations found in the target tissues were detectable in all samples from the 1st until the 14th day after medication, with higher concentrations in kidney and liver ranging from 838.88 μg/kg to 39.18 μg/kg and from 1988.77 μg/kg to 16.58 μg/kg between the 1st and the 14th day, respectively. Concentrations in muscle and fat, the 1st day after medication, were 233.96 μg/kg and 173.89 μg/kg, respectively and the 4th day they were dropped below the maximum residue limit (MRL), which means that sheep tissues are safe for the consumer. A withdrawal time of 13 days was determined for liver, the main organ used for this calculation.